The impact of service and hearing dogs on health-related quality of life and activity level: a Swedish longitudinal intervention study - Martina Lundqvist; Lars-Åke Levin; Kerstin Roback; Jenny Alwin (BMC, 2018)
Abstract Background Individuals with severe disability often require personal assistance and help from informal caregivers, in addition to conventional health care. The utilization of assistance dogs may decrease the need for health and social care and increase the independence of these individuals. Service and hearing dogs are trained to assist specific individuals and can be specialized to meet individual needs. The aim of this study was to describe and explore potential consequences for health-related quality of life, well-being and activity level, of having a certified service or hearing dog. Methods A longitudinal interventional study with a pre-post design was conducted. At inclusion, all participants in the study had a regular (untrained) companion dog. Data were collected before training of the dog started and three months after certification of the dog. Health-related quality of life was assessed with EQ-5D-3L, EQ-VAS and RAND-36. Well-being was measured with WHO-5 and self-esteem with the Rosenberg Self-Esteem Scale. In addition, questions were asked about physical activity and time spent away from home and on social activities. Subgroups were analyzed for physical service and diabetes alert dogs. Results Fifty-five owner-and-dog pairs completed the study (30 physical service dogs, 20 diabetes alert dogs, 2 epilepsy alert dogs, and 3 hearing dogs). Initially, study participants reported low health-related quality of life compared with the general population. At follow-up, health-related quality of life measured with the EQ-VAS, well-being and level of physical activity had improved significantly. In the subgroup analysis, physical service dog owners had lower health-related quality of life than diabetes alert dog owners. The improvement from baseline to follow-up measured with EQ-5D statistically differed between the subgroups. Conclusions The target population for service and hearing dogs has an overall low health-related quality of life. Our study indicates that having a certified service or hearing dog may have positive impact on health-related quality of life, well-being and activity level. Service and hearing dogs are a potentially important "wagging tail aid" for this vulnerable population, able to alleviate strain, increase independence, and decrease the risk of social isolation. Trial Registration The trial was retrospectively registered in http://clinicaltrial.gov, NCT03270592. September, 2017.